Roe deer habitat selection in Spain: constraints on the distribution of a species - Virgos, E; Tellería, J L (Canadian Journal of Zoology, 1998)
This study analyzes the role of summer habitat selection in determining the distribution of a population of roe deer (Capreolus capreolus L.) in central Spain, where surplus individuals have emigrated from mountains to the surrounding plateaus during the last decade. The species was more abundant in the mesic mountain forests (Scots pine (Pinus sylvestris), Pyrenean oak (Quercus pyrenaica)) than in the xeric, sclerophyllous holm oak (Quercus ilex) forests of surrounding plateaus. Roe deer prefer patches occupied by brambles (Rubus spp.) and rose bushes (Rosa spp.) and patches with higher cover on pastures and moors (Erica spp. and Calluna spp.). These vegetation types are linked to moist soils in the Mediterranean zone, indicating that roe deer prefer the moister, more productive patches. Roe deer actively selected productive patches covered by leguminous shrubs (Sarothamnus, Retama) and rejected poor patches covered by Cistus ladanifer and Cistus laurifolius (two shrubs that produce chemicals toxic to other plants). Low summer primary productivity of xeric, sclerophyllous forests can explain the low abundance of roe deer in these forests. This supports the view that habitat constraints limit numbers and distribution of this Palaearctic species at the southern edge of its range.
doi: 10.1139/z98-065
Keywords: habitat selection; leguminous shrubs (PG); roe deer